American exceptionalism in a new light: a comparison of intergenerational earnings mobility in the Nordic countries, the United Kingdom and the United States - Markus Jäntti (Institute for the Study of Labor (IZA), 2006)
We develop methods and employ similar sample restrictions to analyse differences in intergenerational earnings mobility across the United States, the United Kingdom, Denmark, Finland, Norway and Sweden. We examine earnings mobility among pairs of fathers and sons as well as fathers and daughters using both mobility matrices and regression and correlation coefficients. Our results suggest that all countries exhibit substantial earnings persistence across generations, but with statistically significant differences across countries. Mobility is lower in the U.S. than in the U.K., where it is lower again compared to the Nordic countries. Persistence is greatest in the tails of the distributions and tends to be particularly high in the upper tails: though in the U.S. this is reversed with a particularly high likelihood that sons of the poorest fathers will remain in the lowest earnings quintile. This is a challenge to the popular notion of 'American exceptionalism'. The U.S. also differs from the Nordic countries in its very low likelihood that sons of the highest earners will show downward 'long-distance' mobility into the lowest earnings quintile. In this, the U.K. is more similar to the U.S..
Keywords: J62; C23; 330; intergenerational mobility; earnings inequality; long-run earnings